ANALYSIS OF THE ANTIOXIDANT ACTIVITY OF GERANIOL EMPLOYING VARIOUS IN-VITRO MODELS: RELEVANCE TO NEURODEGENERATION IN DIABETIC NEUROPATHY - Prasad, Sathya N; Muralidhara, Murali (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to analyze antioxidant effect of geraniol (GE) in different in vitro models. Methods: Initially, the antioxidant activity of GE was assessed by diphenyl picrylhydrazyl radical (DPPH) assay. The modulatory effect of GE against 2,2'-azobis(2-amidinopropane) dihydrochloride induced lipid peroxidation in rat brain regions (cortex and cerebellum) and sciatic nerve (SN) homogenates was determined. Further, the effect of GE was assessed against hyperglycemia-induced oxidative stress (OS) in SHSY5Y, a human neuroblastoma cell line. Results: GE proved to be a good scavenger of DPPH free radical (inhibitory concentration 50% [IC50] value = 663 nmol) and could lower the lipid peroxidation levels in rat brain tissue and SN homogenates (25-40%). Further, it rescue the SHSY5Y cells from hyperglycemia-induced death. Co-exposure of GE with the IC50 level of glucose (100 mM) lowered the levels of reactive oxygen species, hydrogen peroxides and 3-nitrotyrosine levels with concomitant elevation in the glutathione levels (about two folds). Conclusion: Collectively from these findings and other studies previously conducted (from our lab and others) emphasize the potential benefit of GE against OS, a progressive pathological feature of neurodegenerative disorders. Â 